Purification, characterization, and crystallization of a deoxynivalenol-detoxifying glutathione transferase from Trichoderma reesei - Pyysalo, Julia (My University, 2024)
Fusarium graminearum is one of the most threatening fungal pathogens in agriculture. It causes devastating annual yield losses, and the number of reported cases has increased in recent years owing to climate change and the rise of improper farming practices. The fungus produces a plethora of trichothecenes, the most important of which is deoxynivalenol (DON). It is a virulence factor that inhibits protein synthesis in wheat crops. Fungicides have been used to combat F. graminearum infection, but their effectiveness depends on the timing of application. Moreover, the rise of fungicide-resistant fungi has increased the need for new methods to combat infections. One possibility is to use glutathione transferases (GSTs). GSTs are a superfamily of enzymes that detoxify a wide range of compounds. GSTs are produced by many organisms and are important phase II detoxification enzymes. The catalytic mechanism of GSTs involves the conjugation of glutathione (GSH) to hydrophobic compounds, making them more soluble. Wood-degrading fungi produce many GSTs that bind and detoxify various compounds. A GST from Trichoderma reesei (TrGST) has been shown to bind and detoxify DON with high affinity. It belongs to the fungal specific GST class A (GSTFuA) class of GSTs. This thesis aimed to further characterize TrGST. Enzyme stability, binding affinity with and without GSH, and binding sites were studied using mass photometry, isothermal titration calorimetry, and crystallization with DON and its adduct DON-13-GSH. TrGST has the characteristics of a GSTFuA class GST and forms a dimeric structure. It binds DON with and without GSH with binding affinities of 2.5 x 10-7 M and 3.6 x 10-6 M, respectively. The presence of GSH causes a conformational change in TrGST. Microneedles were produced with DON and DON-13-GSH in complex with TrGST during crystallization trials.
Keywords: Fusarium graminearum, trichothecene, glutathione transferase, Trichoderma reesei, characterization, mass photometry, isothermal titration calorimetry, crystallization